2016
DOI: 10.1016/j.jchromb.2015.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol as a natural probe for free radical-mediated lipid peroxidation in biological membranes and lipoproteins

Abstract: We describe a relatively convenient and reliable procedure for assessing the magnitude of free radical-mediated (chain) lipid peroxidation in biological systems. The approach is based on use of radiolabeled cholesterol ([14C]Ch) as a probe and determination of well-resolved oxidation intermediates/products ([14C]ChOX species), using high performance thin layer chromatography with phorphorimaging detection (HPTLC-PI). In a lipid hydroperoxide-primed liposomal test system treated with ascorbate and a lipophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Cholesterol, one of the components of the membrane, plays a crucial role in maintaining the integrity of the cell membrane [ 22 ]. In addition, cholesterol was reported to accumulate in specific domains of the membrane and combine with sphingolipids, which formed compartmentalized and highly stable micro-domains termed lipid-rafts [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol, one of the components of the membrane, plays a crucial role in maintaining the integrity of the cell membrane [ 22 ]. In addition, cholesterol was reported to accumulate in specific domains of the membrane and combine with sphingolipids, which formed compartmentalized and highly stable micro-domains termed lipid-rafts [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A great improvement came with the authors’ introduction of two highly sensitive and specific new approaches: (i) high performance liquid chromatography with mercury cathode electrochemical detection (HPLC-EC(Hg)) for analyzing individual ChOOHs [1416] and (ii) high performance thin layer chromatography with phosphorimaging detection (HPTLC-PI) for analyzing [ 14 C]ChOX [17,18]. Using HPLC-EC(Hg), we found that tracking growth of the 7α/7β-OOH signal and decline of the initial 5α-OOH signal provided an excellent means of assessing LOOH-initiated chain peroxidation in cells photodynamically stressed with 1 O 2 [19].…”
Section: One-electron Reduction Of Lipid Hydroperoxidesmentioning
confidence: 99%
“…Transfer rate can be increased using a protein transporter such as recombinant sterol carrier protein‐2 (SCP‐2), which is easily removed sufficient transfer uptake is achieved. For mammalian cells, most of the [ 14 C]Ch transferred in this way will reside in the plasma membrane, allowing chain peroxidation activity to be probed specifically in this compartment . Another plus about using [ 14 C]Ch is that it avoids the potential artifacts associated with exogenous probes such as spin traps and fluorophores , which might perturb lipid organization or act as antioxidants in systems being studied.…”
Section: Cholesterol As a Mechanistic Probe And Chain Peroxidation Rementioning
confidence: 99%
“…During chain reactions induced by an oxidative challenge in the presence of reducible metal ions or reductive turnover of pre‐existing LOOHs, the probe gives rise to [ 14 C]ChOX species. The latter are conveniently detected and quantified by high‐performance thin layer chromatography with phosphorimaging detection (HPTLC‐PI) . Individual ChOX species include redox‐active 7 α / β ‐OOH as well as redox‐inactive 7 α / β ‐OH, 7‐ketone, and 5,6‐epoxide.…”
Section: Cholesterol As a Mechanistic Probe And Chain Peroxidation Rementioning
confidence: 99%
See 1 more Smart Citation